KNOWLEDGE, ATTITUDES, AND BEHAVIOR OF PARENTS TO THE METHOD OF UPBRINGING CHILDREN WHO HAVE DOWN SYNDROME IN SLB-C TUNAS HARAPAN KARAWANG - Dwinindita, Lizsa Y; Ivone, July; Supantini, Dedeh (Journal of Medicine and Health, 2018)
Down syndrome is a genetic disorder characterized by an excess of third chromosome in the 21st pair of chromosomes that causes the number of chromosomes to be 47. The method of parenting is a way of caring, nurturing and educating, therefore parents should have knowledge, attitude and good method of behavior parenting. The highest prevalence of Down syndrome is in West Java, which is around 50.90%. The aim of the research is to recognize the level of knowledge, attitudes, and behavior of parents to the method of upbringing children who have Down syndrome in SLB-C Tunas Harapan Karawang. The research method used in this research is descriptive, cross sectional design with research instrument in the form of questionnaire containing 30 questions. Research subjects were all parents of Down syndrome children in SLB-C Tunas Harapan Karawang with 52 respondents. The result of the research is 90,4% of respondents have good knowledge, 98,2% of respondents have good attitude, and 96,1% of respondents have good behavior. The conclusion of this research is the level of knowledge, attitude, and behavior of parents who have Down syndrome children in SLB-C Tunas Harapan Karawang generally is good.     Keywords: down syndrome, parents, upbringing